MENGUNGKAP IDEOLOGI DI BALIK SELERA: ANALISIS WACANA KRITIS PADA IKLAN VIDEO GOFOOD DAN GRABFOOD - Rosita, Eva; Solihati, Nani (STKIP Siliwangi, 2024)
This study critically analyzes the food delivery digital (video) advertisements by GoFood and GrabFood in Indonesia using Norman Fairclough's Critical Discourse Analysis approach. It aims to uncover how language in these advertisements shapes social reality and communicates specific ideologies to consumers. Through text analysis, discursive practices, and socio-cultural context, the study evaluates how these advertisements serve as promotional tools and embed social values and norms influencing consumer identity and behavior. The qualitative descriptive methodology focuses on GoFood and GrabFood YouTube advertisments, highlighting the strategic use of language and visual representation. Findings indicate that GoFood “Breaking News” and GrabFood “Hematematika” advertisements optimize linguistic and structural elements to convey ideologies of efficiency and modernity. The discussion explores the implications of these findings within social and cultural practices and their impact on economic and social dynamics. The study contributes to developing more inclusive and representative communication strategies in digital marketing. Further research should investigate similar advertisements in different cultural contexts to understand the broader impact.